Acoustical and viscometric studies of buspirone hydrochloride with cobalt(II) and copper(II) ions in aqueous medium. Issue 1 (1st January 2017) - Tiwari, Sandeep; Kusmariya, Brajendra S.; Tiwari, Anjali; Pathak, V.; Mishra, A.P.
Abstract: Ultrasonic velocity measurements, density measurements and viscometric studies were conducted for the drug buspirone hydrochloride (0.01–0.1 M) at three different concentrations (0.1, 0.05 and 0.025 M) at 298.15 K/1 atm. The buspirone hydrochloride was prepared in aqueous solutions of Cu(II) and Co(II) metal ion. The experimental data were used to determine acoustical parameters, such as isentropic compressibility, intermolecular free length, specific acoustic impedance, relative association, free volume, internal pressure, viscous relaxation time, Gibb's free energy, attenuation coefficient, Rao's constant, and Wada's constant. The viscosity data were analysed using the Jones–Dole equation, and the values of the Falkenhagen coefficient A and Jones–Dole B -coefficient were calculated. The outcomes were expressed in terms of the molecular interactions and the variations in parameters under varying solute concentrations. Concluding remarks regarding intermolecular interactions are provided.